2017
DOI: 10.1016/j.jvs.2016.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical site infection after open lower extremity revascularization

Abstract: SSI after LEB is associated with an increase in rate of amputation and reoperation. Several patient, operative, and hospital-related risk factors that predict postoperative SSI were identified, suggesting that targeted improvements in perioperative care may decrease complications and improve vascular patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 57 publications
2
33
0
4
Order By: Relevance
“…26 Although no study has directly studied SSI following EVAR, the study by Davis et al did identify renal failure as a significant risk factor for SSI in their study of 3,033 patients following open lower extremity bypasses (OR 4.35; 95% CI: 2.74-6.72, p < 0.001). 27 O'Hare et al also revealed higher wound infections in patients with severe renal failure (on dialysis) following NSQIP-documented lower extremity revascularization. 28 The association of COPD with wound complications following oEVAR was also an expected finding due to its previous association with SSI in other types of vascular surgery such as lower extremity bypass.…”
Section: Discussionmentioning
confidence: 97%
“…26 Although no study has directly studied SSI following EVAR, the study by Davis et al did identify renal failure as a significant risk factor for SSI in their study of 3,033 patients following open lower extremity bypasses (OR 4.35; 95% CI: 2.74-6.72, p < 0.001). 27 O'Hare et al also revealed higher wound infections in patients with severe renal failure (on dialysis) following NSQIP-documented lower extremity revascularization. 28 The association of COPD with wound complications following oEVAR was also an expected finding due to its previous association with SSI in other types of vascular surgery such as lower extremity bypass.…”
Section: Discussionmentioning
confidence: 97%
“…A high rate of foot ulcer infection and wound infection can in fact be found in HD patients and this can be assumed to be the cause of the subsequent TCC infection. In particular, a study by Davis et al 17 on 3033 patients who underwent major surgery for peripheral arterial disease showed that HD patients had a four times higher risk for surgical site infection, which was in turn associated with reoperation and amputation.…”
Section: Discussionmentioning
confidence: 99%
“…35 He received 40 cc of CaSO 4 (Stimulan; Biocomposites, Staffordshire, England), which constitutes 4 packages of the product. 35 It is therefore important for providers to be cognizant of their patient's clinical status and the risk of elevating serum calcium when using high volumes of CaSO 4 .…”
Section: Safetymentioning
confidence: 99%
“…1 Higher rates are reported in traumatic injuries (20%-50%) or in some elective populations, including high-risk vascular surgery patients (15% or greater). 2-6 Surgical site infection can significantly increase cost and morbidity. 1 Morbidity, however, can be magnitudes higher when it involves prosthetic material.…”
Section: Introductionmentioning
confidence: 99%